2007
DOI: 10.1089/cbr.2007.369
|View full text |Cite
|
Sign up to set email alerts
|

Direct Targeting of Tumor Cell F1F0 ATP-Synthase by Radioiodine Angiostatin In Vitro and In Vivo

Abstract: Neurotensin (NT) receptors are overexpressed in different human tumors, such as human ductal pancreatic adenocarcinoma. New stable neurotensin analogs with high receptor affinity have been synthesized by replacing arginine residues with lysine and arginine derivatives. The aim of this study was to explore the biodistribution, tumor uptake, kidney localization, and stability characteristics of these new analogs in order to develop new diagnostic tools for exocrine pancreatic cancer. Four (111)In-labeled DTPA-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Otherwise, for example, the mitochondrial superoxide dismutase would have been highlighted. This is consistent with the hypothesis that the oxidative damage may derive from an OxPhos dysfunction both inside the mitochondria and in ectopic locations, that has been reported in plasma membranes, 41‐45 myelin sheath, rod disks, exosomes, and MV 17,46‐48 . The expression of mitochondrial components of the electron transfer chain (ETC) and F o F 1 ‐ATP synthase in ectopic sites not protected by a double membrane poses greater risks for oxidative stress generation and implies the involvement of GSS.…”
Section: Discussionsupporting
confidence: 90%
“…Otherwise, for example, the mitochondrial superoxide dismutase would have been highlighted. This is consistent with the hypothesis that the oxidative damage may derive from an OxPhos dysfunction both inside the mitochondria and in ectopic locations, that has been reported in plasma membranes, 41‐45 myelin sheath, rod disks, exosomes, and MV 17,46‐48 . The expression of mitochondrial components of the electron transfer chain (ETC) and F o F 1 ‐ATP synthase in ectopic sites not protected by a double membrane poses greater risks for oxidative stress generation and implies the involvement of GSS.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, several authors have demonstrated that the angiostatin which binds and inhibits F o F 1 -ATP synthase on the endothelial cell surface (Chi and Pizzo 2006a), blocks tumor angiogenesis in vivo (Jung et al 2007;Moser et al 2001), inhibiting the endothelial cell migration and proliferation (Moser et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggested that ectopic ATP synthase localized to the caveolae of the cell membrane, with the F1 portion directed into the extracellular space. Some studies have also reported that other subunits of the ATP synthase, such as the α and β subunits of the F1 domain and the β-and δ-subunits of F0, can be found on the outside of the membranes of tumor cells and some types of normal cells, including hepatocytes, keratinocytes, adipocytes, endothelial cells and cardiomyocytes (21)(22)(23)(24), suggesting that translocation is possible. The enzyme may therefore be called cell surface ATP synthase or ecto-ATP synthase (ecto-ATPase, ecto-F1-ATPase), and ectopically localized ATP5B may be called ecto-ATP5B.…”
Section: Discussionmentioning
confidence: 99%